Assessment of nutritional status in relation to socio-economic status during the COVID-19 pandemic in early childhood in Morocco - Benayad, Fatima Zohra; Razine, Rachid; Barich, Fatima; Laamiri, Fatima Zahra; Haroun, Abbas Ermilo; El Hilali, Samia; Obtel, Majdouline (European Journal of Clinical and Experimental Medicine, 2024)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. The objective of this study is to evaluate the nutritional status of children aged 0-24 months, and analyze its association with socioeconomic status during the COVID-19 pandemic in Morocco. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. This cross-sectional study was carried out in the outpatient health network between 2021 and 2022, by taking anthropometric measurements of children in accordance with World Health Organization standards and using a questionnaire sent to consenting mothers. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. 1012 children were included in this study. The prevalence of overweight was 13.3%, obesity 3.2%, wasting and severe wasting 2.7%. The study revealed that boys had a higher prevalence of overweight compared to girls (p=0.01), while girls were more likely to have a normal weight than boys (p=0.001). Furthermore, a statistically significant association was observed between nutritional status and age in boys (p=0.003); however, malnutrition such as overweight and wasting increased after the age of 12 months in both genders. There was a significant correlation between child nutritional status, gender, and residence, but no significant association was found with parental education or household income. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. This study suggests that it is important to develop strategies to improve socio-economic status in the aftermath of the COVID-19 pandemic.